2022
DOI: 10.3390/mi13050669
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Broadband Tunable Terahertz Metamaterial Absorber Based on Double-Layer Vanadium Dioxide Square Ring Arrays

Abstract: Based on the phase transition of vanadium dioxide(VO2), an ultra-broadband tunable terahertz metamaterial absorber is proposed. The absorber consists of bilayer VO2 square ring arrays with different sizes, which are completely wrapped in Topas and placed on gold substrate. The simulation results show that the absorption greater than 90% has frequencies ranging from 1.63 THz to 12.39 THz, which provides an absorption frequency bandwidth of 10.76 THz, and a relative bandwidth of 153.5%. By changing the electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…From the figure, it can be observed that when the conductivity of VO 2 reaches 2 × 10 5 S m −1 , the real part of the relative impedance of the absorber is close to 1 and the imaginary part is almost 0 in the frequency range from 1.99 THz to 6.19 THz. This result clearly shows that the impedance of the absorber has reached a state of almost perfect matching with the impedance of the free space in this frequency range [43], which minimizes the reflection and significantly improves the absorber's performance in absorbing electromagnetic waves [44].…”
Section: Discussionmentioning
confidence: 75%
“…From the figure, it can be observed that when the conductivity of VO 2 reaches 2 × 10 5 S m −1 , the real part of the relative impedance of the absorber is close to 1 and the imaginary part is almost 0 in the frequency range from 1.99 THz to 6.19 THz. This result clearly shows that the impedance of the absorber has reached a state of almost perfect matching with the impedance of the free space in this frequency range [43], which minimizes the reflection and significantly improves the absorber's performance in absorbing electromagnetic waves [44].…”
Section: Discussionmentioning
confidence: 75%
“…1 In thermal optoelectronics, thermal imaging and thermal emission, the need for broadband and omnidirectional absorbers with thin and compact structures is urgent. 2 Therefore, the emergence of MPAs perfectly meets this need.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 In recent years, absorber structures based on graphite resonators have been reported to achieve broadband THz absorption, but they cannot be dynamically tuned. [36][37][38] So far, some multilayer graphene-based structures, 39 multilayer VO 2 -based structures, 40 or multilayer metal/dielectric structures 41 have been designed to achieve tunable ultra-wideband absorption bandwidth. However, these structures greatly increase the difficulty of manufacturing, and the performance of devices is not reliable due to the characteristics of metals in certain environments.…”
Section: Introductionmentioning
confidence: 99%